2012
DOI: 10.1186/1475-9276-11-80
|View full text |Cite
|
Sign up to set email alerts
|

Who experiences discrimination in Brazil? Evidence from a large metropolitan region

Abstract: IntroductionPerceived discrimination is related to poor health and has been offered as one explanation for the persistence of health inequalities in some societies. In this study, we explore the prevalence and correlates of perceived discrimination in a large, multiracial Brazilian metropolitan area.MethodsThe study uses secondary analysis of a regionally representative household survey conducted in 2010 (n=12,213). Bivariate analyses and multiple logistic regression assess the magnitude and statistical signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 45 publications
5
43
1
12
Order By: Relevance
“…The frequency of self-reported discrimination in this study (65.8%) was relatively higher than in three other Brazilian studies, which estimated a prevalence of 16.4% among adolescents, 31 9% among a general adult population 32 and 34.7% among public civil servants. 33 The prevalence of self-reported discrimination was also higher than that found in studies that enrolled immigrants 9 and Latinos 34 in the United States; in both, the prevalence of discrimination was about 30.0%.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The frequency of self-reported discrimination in this study (65.8%) was relatively higher than in three other Brazilian studies, which estimated a prevalence of 16.4% among adolescents, 31 9% among a general adult population 32 and 34.7% among public civil servants. 33 The prevalence of self-reported discrimination was also higher than that found in studies that enrolled immigrants 9 and Latinos 34 in the United States; in both, the prevalence of discrimination was about 30.0%.…”
Section: Discussioncontrasting
confidence: 78%
“…In addition, the techniques adopted to approach the interviewees in each study varied substantially. For instance, Macinko et al 32 and Gonçalves et al 31 administered face-toface questionnaires, whereas our investigation used self-administered instruments. The investigation of a sensitive topic, such as discrimination, using face-to-face interviews may have contributed to the underestimation of the phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the extant research on perceived discrimination has been conducted in the United States, a society with a long history of institutionalized racial discrimination, but one that experienced a Civil Rights movement in the 1960s that led to legal restrictions on racial discrimination, and a need to monitor compliance with these new laws. Researchers in other societies have also begun to explore the prevalence of perceived racial discrimination in the context of their own distinctive social and legal histories around race, such as South Africa 3 and Brazil 4,5,6,7 . Brazil stands out as a society without racially-discriminatory laws after the abolition of slavery, and a unique reputation as a supposed "racial democracy" as compared to other multiracial societies, but only recently has begun to officially acknowledge the persistence of racebased inequalities and discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…A 2010 sample of adults in Belo Horizonte (Minas Gerais State) showed that 15% of Blacks felt they were victim of any type of discrimination, compared to about 8% of Brown or White Brazilians 4 . A higher percentage of Black and Brown adolescents in Pelotas (Rio Grande do Sul State) reported that during the past year from interview, they felt discriminated against or damaged because of "color or race; religion or cult; poverty or wealth; disease or physical disability" as compared to white peers 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, não se pode descartar limitações inerentes a estudos étnico-racial como as diferenças idiossincráticas na autodeterminação racial e na percepção de racismo 47 , como explicativas da associação estatisticamente significativa verificada na categorização original. As complexidades das pesquisas étnico-raciais na área de saúde foram também apontadas por um estudo recente de Macinko et al 48 , que, ao analisarem o resultado de uma pesquisa de 12.930 residentes da Região Metropolitana de Belo Horizonte, Minas Gerais, verificaram que a probabilidade prevista de declarar ter sido vítima de discriminação foi maior para homens e mulheres com saúde ruim que se autodeclararam com pretos (31% e 35%, respectivamente). Entretanto, segundo os autores, raça/cor foi apenas uma das variáveis associadas com discriminação, o que pode indicar a complexidade da relação entre raça/cor, discriminação e saúde.…”
Section: Discussionunclassified